As condições de produção dos discursos de identidade: um estudo sobre os jovens militantes do MST - Tarini, Ana Maria de Fátima Leme (2007)
This essay presents an analysis of the building process of young landless people identities, students of the technical course in Agro environment held on the settlement Antônio Companheiro Tavares, in the town of São Miguel do Iguaçu- Paraná. The case study is subsided by philosophical pedagogical foundations adopted in the educational formation of the selected youngsters and can be used as parameters for the identification and/or justification of the identities built by the Movimento dos Trabalhadores Rurais Sem Terra (MST) on their space of historical and identity formation. We search - on self identification of the subject students - to understand the dynamics of the process of construction of identity under the sociological an linguistics joint comprehending two theoretical axles: studies of identity and discourse, in which are jointed the threads of French speech theory and sociology s socio cultural studies. Such presuppositions allow the understanding of who these youngsters are, how they identify themselves and the reason why they do it are also analyzed. Some discursive practices also analyzed, which are given by individual and collective oral interviews: field observation registers; collection of school writing works and information on reflection notebooks of the young students - the production conditions and the silences in composition of their identify discourses. By proposing a look to the identify discourse of the young landless people we search to join subject, discourse and history, which build and give sense to history through its discourses. Under this perspective, we conceive that discursive happenings are fossilized in the cultures of each society (FOUCAULT, 2005) and that - in order to capture them - it is necessary to take a huge field of possibilities constituted by the set of all the spoken or written statements in its dispersion of happenings and in the own instance of each one of them (GREGOLIN, 2004). Being so, the investigation revealed that the social relations with family members, neighbors, real and virtual friends, in short, all the relations suggest the identity formation. However, by assuming the identity the young students of the mentioned settlement suggest the preference for the same form of identification, that is: landless young people.